2022
DOI: 10.3389/fphys.2022.913369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Disorders and Circadian Rhythm Changes on Male Reproductive Health: A Systematic Review and Meta-analysis

Abstract: Objectives: The purpose of this study was to elucidate the relationship between sleep disorders and male reproductive health, and to explore the underlying mechanisms via a systematic review and meta-analysis.Methods: PubMed, Embase, The Cochrane library, Web of Science, Scopus databases were searched to collect clinical research on the effects of sleep disorders on male semen parameters from inception to February 24, 2022. RevMan 5.4 was used for meta-statistical analysis. Stata16 software was used to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…18 Other biomarkers of male fecundity, such as testes volume or reproductive hormone levels, have been rarely studied in relation to sleep duration. 4,5 One cross-sectional study from the United States found no association between self-reported sleep duration and testes volume, however, when measuring sleep duration using actigraphy, the authors found a linear association between sleep duration and testes size. 12 In another study from the United States, the shorter sleep duration was associated with lower testosterone levels in men aged 16−80 years old, 19 whereas in a Danish cross-sectional study, the longer sleep duration was associated with lower levels of testosterone in middle-aged men.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…18 Other biomarkers of male fecundity, such as testes volume or reproductive hormone levels, have been rarely studied in relation to sleep duration. 4,5 One cross-sectional study from the United States found no association between self-reported sleep duration and testes volume, however, when measuring sleep duration using actigraphy, the authors found a linear association between sleep duration and testes size. 12 In another study from the United States, the shorter sleep duration was associated with lower testosterone levels in men aged 16−80 years old, 19 whereas in a Danish cross-sectional study, the longer sleep duration was associated with lower levels of testosterone in middle-aged men.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Sleep disturbances such as late bedtime, shift work, and low quality sleep may pose such risk factors. [3][4][5][6][7][8] Moreover, epidemiological findings suggest that short and long sleep duration might be associated with biomarkers of poor male fecundity too; however, results are inconsistent (for an overview of the epidemiological literature, please see Table S1). [3][4][5][9][10][11][12][13][14][15][16][17] Some studies of young Chinese men report an inverse u-shaped association between sleep duration and semen characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations